Planning effective instruction - Kay M. Price (Thomson/Wadsworth, 2007)
Featuring a new organization and expanded discussion of curriculum, instruction, and management, the Third Edition of PLANNING EFFECTIVE INSTRUCTION even more fully equips readers for teaching in ways that meet the needs of all students in today's diverse classroom. The four-part re-organization corresponds with a new framework for diversity-responsive teaching that helps focus planning for diversity. Represented by a visual organizer, this framework helps readers see how what you teach, how you teach, and the context for teaching interact to bring about the success of all students